Wikileaks: the Backstage of Power - Serra, Marcello (Estudios sobre el Mensaje Periodístico, 2012)
The article discusses the impact of Wikileaks and other similar projects on the world of politics and information. These themes are tackled putting aside the value of the leaks, following the idea that the real content of Wikileaks is its form. In particular, it analyses how exposure of the backstage in certain spheres of power could give citizens the ability to invigilate the institutions. One important theme is the ability to solve the possible information overload produced by the large quantity of leaks; a phenomenon which, on one hand, causes changes in investigative journalism and, on the other, appeals to the interpretative ability of the modern general intellect.